INTEGRATING HUMAN RESOURCE CONCEPTS INTO DIGITAL MARKETING STRATEGIES: A COMPREHENSIVE APPROACH FOR ORGANIZATIONAL SUCCESS (International Journal of Food and Nutritional Sciences, 2022)
In the rapidly evolving digital marketing landscape, this research explores the symbiotic relationship between digital marketing strategies and human resource (HR) concepts. The study investigates the current digital marketing strategies employed by organizations and delves into the role of HR concepts in fostering employee skills, motivation, and engagement. By exploring the potential synergy between digital marketing and HR practices, the research aims to propose a practical framework for integrating HR concepts into digital marketing strategies effectively.